Designing for effective online Teacher Professional Development (oTPD) in building education by supporting beliefs, communities, collaboration, and development - Godsk, Mikkel; Alopaeus Jelsbak, Vibe; Lund Nielsen, Birgitte (Proceedings of the International Conference on Networked Learning, 2024)
This article reports the initial research findings from a large project on online professional development and upskilling of in-service building teachers’ digital competencies. Based on the results from a preceding literature review and the pilot delivery of the course, three key factors for the design of effective online teacher professional development in building education — beliefs, communities and collaboration, and teaching development — are exemplified and discussed. The article concludes that the pilot was successful in developing the participants’ technical skills and competencies to introduce technology in building education; however, the pilot did not significantly influence the participants’ beliefs nor made them change practice within the duration of the course.